Pathologic Findings in MRI-Guided Needle Core Biopsies of the Breast in Patients with Newly Diagnosed Breast Cancer - K. P. Siziopikou; P. Jokich; M. Cobleigh (International Journal of Breast Cancer)
The role of MRI in the management of breast carcinoma is rapidly evolving from its initial use for specific indications only to a more widespread use on all women with newly diagnosed early stage breast cancer. However, there are many concerns that such widespread use is premature since detailed correlation of MRI findings with the underlying histopathology of the breast lesions is still evolving and clear evidence for improvements in management and overall prognosis of breast cancer patients evaluated by breast MRI after their initial cancer diagnosis is lacking. In this paper, we would like to bring attention to a benign lesion that is frequently present on MRI-guided breast biopsies performed on suspicious MRI findings in the affected breast of patients with a new diagnosis of breast carcinoma.